Gold nanospirals1. Issue 92 (8th October 2015) - Chang, Yu-Hsu; Wu, Yu-Chuan; Hsu, Ya-Ting; Huang, Shih-Hao; Huang, Yi-Chin; Chiu, Hsin-Tien
<x xml:space="preserve">Abstract</x> This study used a galvanic displacement reaction for aluminum-gold oxidation–reduction and added surfactants to act as capping agents to control the morphology and size of gold growth.